The systematic review and meta-analysis evaluated the efficacy and safety of nefopam for catheter-related bladder discomfort based on randomized controlled trials - Chi, Junpeng; Wu, Jinhui; Lou, Keyuan; Ma, Jian; Wu, Jitao; Cui, Yuanshan (Frontiers in Pharmacology, 2023)
Background: CRBD is a frequent occurrence following urinary catheterization during surgical procedures, as well as a commonly experienced bladder pain syndrome after surgery. We conducted a meta-analysis to assess the efficacy and safety of nefopam for managing postoperative CRBD.A systematic search of PubMed, Embase, Cochrane Library, and Web of Science was conducted to find randomized controlled trials (RCTs) on using nefopam in postoperative CRBD. Data analysis was performed using RevMan version 5.4.1.Results: Five RCTs with 405 patients were analyzed to evaluate the efficacy of nefopam on postoperative CRBD. Short-term and long-term periods were defined as within 6 hours and longer than 12 hours after surgery, respectively. The incidence and severity of CRBD were compared between the two groups during these time periods. The analysis proved that nefopam reduced the short-term incidence of postoperative CRBD (RR 0.36; 95% CI, 0.18-0.70; p = 0.003, I 2 = 78%) and the long-term incidence (RR 0.49; 95% CI, 0.32-0.74; p = 0.007, I 2 = 0%) significantly. We compared the incidence of moderate-to-severe CRBD between groups based on the scaling system (none, mild, moderate, and severe). This was used to assess the severity of postoperative CRBD. The results showed that patients in the nefopam group had a significantly lower incidence of moderate-to-severe CRBD compared to those in the placebo group in the short-term (RR 0.19; 95% CI, 0.10-0.34; p < 0.00001; I 2 = 0%). However, there were no significant differences between the two groups in the incidence of moderate-to-severe CRBD in the long-term (RR 0.61; 95% CI, 0.21-1.76; p = 0.36; I 2 = 0%). There were no significant variations in the occurrence of adverse events between the nefopam and control groups, mainly including postoperative nausea and vomiting (PONV) (RR 1.14; 95% CI, 0.40-3.21; p = 0.81), and tachycardia (RR 0.25; 95% CI, p=0.20).The findings of this meta-analysis indicate that nefopam significantly reduced the incidence of short or long-term postoperative CRBD. Nefopam decreased the severity of postoperative CRBD, particularly significantly reducing the occurrence of moderate to severe CRBD in the short-term. Overall, patients have good tolerance and no apparent side effects.